2021
DOI: 10.18517/ijaseit.11.1.11211
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Characters of Local Origin Durian (Durio zibethinus Murr.) Fruits and Seeds from Central Tapanuli Regency, North Sumatra, Indonesia

Abstract: Most of the diversity resource of durian was reported existing in Central Tapanuli. Due to local durian potential, germplasm needed to obtain information on the potential for superior cultivars. Here, we report our identification of morphology characteristics to the genetic relationship of local durian to determine the best durian. This research applied exploration study, interviews, descriptive, and qualitative identification. Research data were grouped based on similarity values using cluster analysis. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…It is pointed out by diversity index values of 0.389 and 0.324, respectively (Tables 2 and 3). Such level of diversity was also reported by Sihaloho et al (2021) from durian varieties of Central Tapanuli Regency, North Sumatra, Indonesia, and from Sawang and Langkahan of North Aceh, Indonesia (Handayani and Ismadi, 2018). According to Gao et al (2017), this case may be due to natural selection, the founder effect, genetic isolation, including inbreeding.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…It is pointed out by diversity index values of 0.389 and 0.324, respectively (Tables 2 and 3). Such level of diversity was also reported by Sihaloho et al (2021) from durian varieties of Central Tapanuli Regency, North Sumatra, Indonesia, and from Sawang and Langkahan of North Aceh, Indonesia (Handayani and Ismadi, 2018). According to Gao et al (2017), this case may be due to natural selection, the founder effect, genetic isolation, including inbreeding.…”
Section: Resultssupporting
confidence: 67%
“…This study aimed to determine the phenotypic diversity and relationship of superior local durian varieties from this region based on morphological markers. While these traits have certain disadvantages, such as multigenic inheritance, time-consuming, and strongly influence by environmental parameters (Wu et al, 2021), they are customary to assess the genetic diversity of durian (Sundari et al, 2019;Sihaloho et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative morphological characters were processed using Microsoft Excel 365 student edition software. The morphological data obtained were used to identify and identify between cultivars to differentiate one from another [15].…”
Section: Evaluation and Data Analysismentioning
confidence: 99%
“…In this study, the assumptions used in the genotype (genetic factors) code for qualitative characters. Quantitative characters are controlled by environmental factors and several minor genes [15]. It has been reported that the QTL locus (quantitative trait locus) regulates the expression of a plant's character, such as s flowering time, seed size, and seed dispersal in maize, rice, and sorghum; and growth habit, photoperiod sensitivity, and dormancy in common bean [17].…”
Section: A Identification Of Morphological Charactersmentioning
confidence: 99%
“…Diversity can be studied using morphological, physiological, anatomical, palynological, cytological, biochemical, embryological, and molecular characteristics [20], [21]. Morphological characters are most often used in identification because they are easy to observe.…”
Section: Introductionmentioning
confidence: 99%